Alone Together: Musicking in the Time of COVID-19 - Bajakian, Aram (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
In this piece, Vancouver-based guitarist Aram Bajakian reflects on the ways in which the outer practice of performing for audiences and the inner practice of solitude are symbiotic for musicians, and the challenge of connecting with listeners in a virtual landscape.